Uji Aktivitas Antioksidan Ekstrak Metanol Daun Ramania (Bouea macrophylla Griffith.) Menggunakan Metode DPPH: Antioxidant Activity Test of Methanol Extract of Ramania Leaf (Bouea macrophylla Griffith.) Using the DPPH method - Dimas Satya Aiyuba; Aditya Noviadi Rakhmatullah; Ratna Restapaty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Humans have a body that is equipped with a defense system that is considered to be an antioxidant which can minimize the damage caused by free radicals. Ramania (Bouea macrophylla Griffith.) is an herbal plant that has antioxidant properties and inhibits free radicals. This study aims to determine what are the active compounds contained in ramania leaves and determine the IC50 value. Maceration extraction method, obtained the yield of extract 42.5699 g, and the content of compounds contained in the extract are flavonoid compounds, saponins, tannins, steroids, and alkaloids. The extract was tested for antioxidant activity using the DPPH radical inhibition method quantitatively using a UV-Vis spectrophotometer with quercetin as a positive control. In testing the antioxidant quercetin with concentrations of 1, 2, 3, 4, 5 ppm, the results were 3.3434 ppm. In the antioxidant test of methanol extract with concentrations of 2, 4, 6, 8, 10 ppm, the results were 6305 ppm. The results obtained IC50 value of 6.305 ppm which is included in the category of very strong antioxidants. It can be concluded that the methanol extract of Ramania leaves has antioxidant activity.